Mechanical and Thermal Properties of Interlocking Bricks Utilizing Wasted Polyethylene Terephthalate - Alaloul, W.S. (Springer, 2020)
Plastic bottles are non-biodegradable material made up of Polyethylene Terephthalate (PET) and takes around 450Â years to get decomposed. In Malaysia, near 13.2 of plastics contribute to municipal solid waste, where 2.5 is PET. To reduce the waste, interlocking bricks manufacture by waste plastic bottles are used to replace the conventional bricks that use cement and clay. The purpose of this research is to reuse plastic bottles comprised of Polyethylene Terephthalate and Polyurethane binder, by manufacturing interlocking brick that helps to reduce the waste on landfills and the pollution. The plastic bottles were shredded and grinded to a size of 0.75Â mm and mixed with the Polyurethane (PU) and theÂ Polymer. The mixedÂ later casted and compacted in the interlocking brick machine mould. The tests performed on the interlocking bricks were compressive strength, impact, flexural strength and thermal conductivity for obtaining the mechanical and thermal properties. The tests values were then keyed into theÂ Response SurfaceÂ MethodologyÂ (RSM) to obtain the optimal PET and PU to verify reliability. Based on the results it is concluded that PET/PU of 60/40 ratio is suitable as non-load bearing masonry brick and recommended to be used as partition walls. Â© 2020, The Author(s).